1987
DOI: 10.1111/j.1530-0277.1987.tb01326.x
|View full text |Cite
|
Sign up to set email alerts
|

History of Chronic Alcohol Abuse Is Associated with Increased Nighttime Hypoxemia in Older Men

Abstract: The all-night blood oxygen saturations (SaO2) of 19 older abstaining male alcoholics and 19 healthy age-matched controls were recorded. The alcohol group had significantly lower nighttime mean and minimum oxygen saturations, significantly greater absolute (mean-minimum) SaO2 desaturations, and significantly more desaturations below 90% compared with the control group. Additionally, the alcohol group had significantly more individuals with nighttime SaO2 means below 95% and nighttime SaO2 minimums below 90%. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 10 publications
0
2
2
Order By: Relevance
“…Earlier findings that alcoholic patients exhibit an enhanced amount of sleep-disordered breathing [2,11,28,39,40] were not replicated in the present study. One likely explanation is that increased sleep-disordered breathing is age dependent: Aldrich et al [2] reported that only 3 % of alcoholics below the age of 49 years exhibited sleep-disordered breathing while this abnormality was found in 75 % of the patients with an age over 60 years.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Earlier findings that alcoholic patients exhibit an enhanced amount of sleep-disordered breathing [2,11,28,39,40] were not replicated in the present study. One likely explanation is that increased sleep-disordered breathing is age dependent: Aldrich et al [2] reported that only 3 % of alcoholics below the age of 49 years exhibited sleep-disordered breathing while this abnormality was found in 75 % of the patients with an age over 60 years.…”
Section: Discussioncontrasting
confidence: 78%
“…Furthermore, the amount of the reduction of subjectively experienced sleep quality is prognostic for early relapse in alcohol dependent patients [9,10,19,38]. Several other well-recognized causes of disturbed sleep such as periodic leg movements in sleep (PLMS) and sleep-disordered breathing may also contribute to the sleep disturbances associated with alcohol dependence [1,2,11,28,32,36,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, case reports indicate that treating sleep apnea may improve psychotic symptoms. 9 An association between sleep apnea and substance and alcohol abuse has been reported; [35][36][37][38][39][40] however, we did not find an increased prevalence of substance abuse in the apnea group (3.32%) compared with the non-apnea group (3.28%). The prevalence for alcohol dependence in VHA beneficiaries is reportedly high (11%); 12 however, in our study, the prevalence was only 5.68% in the general VHA population and 5.53% in subjects with sleepapnea diagnoses.…”
Section: Discussioncontrasting
confidence: 59%
“…Thus, for example, sleep apnea and periodic leg movements themselves have been related to psychopathology (Berry et al, 1990; Mosko et al, 1989). Similarly, sleep apnea has been linked to chronic alcohol intake (Vitiello et al, 1987), and periodic leg movements have been found among those with rheumatic pain conditions (Moldofsky, Tullis, & Lue, 1986). Both chronic alcohol use (Kales & Kales, 1984) and medical pain conditions (Prinz, Vitiello, Raskind, & Thorpy, 1990) have been linked to poor sleep in their own right.…”
Section: Discussionmentioning
confidence: 99%